Localization of the third component of complement on the cell wall of encapsulated Staphylococcus aureus M: implications for the mechanism of resistance to phagocytosis. - Wilkinson, B J (1979)
Encapsulated Staphylococcus aureus strains are more virulent than unencapsulated staphylococci, and this phenomenon has been associated with decreased opsonization of encapsulated bacteria by normal human serum. Peptidoglycan, a major cell wall component of S. aureus, has been shown to promote opsonization of this bacterial species by certain components of the serum complement system. However, when the processes of complement activation and opsonization of encapsulated staphylococci have been studied, it has been found that encapsulated bacteria activate complement efficiently and C3 is bacteria associated, yet these organisms are not efficiently phagocytized by human polymorphonuclear leukocytes. In this study, the hypothesis was tested that opsonically active molecules are not on the true external surface of encapsulated organisms but rather are cell wall associated and thus "hidden" from human polymorphonuclear leukocytes. By using immunoelectronmicroscopy, C3 was found to be localized on the cell wall of an encapsulated S. aureus strain after incubation of the organism in normal human serum. When shrinkage of the capsule was prevented by treatment with anticapsular antibody, the C3 was again shown to be cell wall associated and located beneath the bacterial capsule. These results suggest that encapsulated S. aureus may resist phagocytosis because opsonically active C3 molecules are not exposed at the true external surface of the bacterium.